Apigenin analogues as SARS-CoV-2 main protease inhibitors: In-silico screening approach. Issue 2 (1st February 2022) - Farhat, Ameny; Ben Hlima, Hajer; Khemakhem, Bassem; Ben Halima, Youssef; Michaud, Philippe; Abdelkafi, Slim; Fendri, Imen
ABSTRACT: The COVID-19 new variants spread rapidly all over the world, and until now scientists strive to find virus-specific antivirals for its treatment. The main protease of SARS-CoV-2 (M pro ) exhibits high structural and sequence homology to main protease of SARS-CoV (93.23% sequence identity), and their sequence alignment indicated 12 mutated/variant residues. The sequence alignment of SARS-CoV-2 main protease led to identification of only one mutated/variant residue with no significant role in its enzymatic process. Therefore, M pro was considered as a high-profile drug target in anti-SARS-CoV-2 drug discovery. Apigenin analogues to COVID-19 main protease binding were evaluated. The detailed interactions between the analogues of Apigenin and SARS-CoV-2 M pro inhibitors were determined as hydrogen bonds, electronic bonds and hydrophobic interactions. The binding energies obtained from the molecular docking of M pro with Boceprevir, Apigenin, Apigenin 7-glucoside-4'-p-coumarate, Apigenin 7-glucoside-4'-trans-caffeate and Apigenin 7-O-beta-d -glucoside (Cosmosiin) were found to be −6.6, −7.2, −8.8, −8.7 and −8.0 kcal/mol, respectively. Pharmacokinetic parameters and toxicological characteristics obtained by computational techniques and Virtual ADME studies of the Apigenin analogues confirmed that the Apigenin 7-glucoside-4'-p-coumarate is the best candidate for SARS-CoV-2 M pro inhibition.